Trailblazers of Global Buddhist Networks - Harding, John S. (Contemporary buddhism, 2016)
This paper surveys the travels and networks of several Buddhist figures early in the modernization of this increasingly global tradition. Revisiting renowned Buddhist representatives, such as Shaku Sōen and Anagarika Dharmapala, reinforces the prominence of principal nodes in this expanding network - both in terms of seminal reformers and crucial arenas of encounter, such as Meiji Japan and Ceylon at the end of the nineteenth century. This study asserts the significant and compounding effect of early cross-cultural encounters at a formative period for modern Buddhism. Although the importance of face-to-face meeting - and the subsequent publications, correspondence, and travels - spanned relationships within and beyond Asia, the paper nevertheless suggests an Asian centre of gravity for Buddhism's modernization and global dissemination.